The association between near‐infrared spectroscopy assessment of microvascular reactivity and flow‐mediated dilation is disrupted in individuals at high risk for cardiovascular disease. (2nd June 2019) - Vieira de Oliveira, Gustavo; Soares, Rogério Nogueira; Volino‐Souza, Mônica; Murias, Juan Manuel; Alvares, Thiago Silveira
Abstract: Objective: This study aimed to evaluate the correlation between the NIRS‐derived reperfusion slope and %FMD in the arm of healthy and at high risk for CVD individuals. Methods: Twelve healthy (24 ± 4 years) and twelve at high risk for cardiovascular disease (65 ± 11 years) individuals participated in the study. The individuals were submitted to a conduit artery FMD followed by a NIRS‐VOT microvascular function test in the arm. Microvascular responsiveness was calculated as the forearm reperfusion slope, and macrovascular function was assessed as the percent of change in FMD (%FMD) of the brachial artery. Results: There was a significant correlation between reperfusion slope and %FMD ( R = 0.61, P < 0.05) in the healthy group; however, no significant correlation between FMD and reperfusion slope ( R = −0.21, P > 0.05) was found in individuals at high risk for CVD. Conclusion: The correlation between NIRS‐derived reperfusion slope and %FMD was disrupted in the arm of individuals at high risk for cardiovascular disease compared to healthy individuals. The findings of the present study reinforce the importance of examining vascular function at microvasculature and conduit artery level, especially in populations with risk factors for CVD.